2011
DOI: 10.21061/ijra.v12i1.1353
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Parabolic Screen Filter on Water Quality and Production of Nile Tilapia (Oreochromis niloticus) and Water Spinach (Ipomoea aquatica) in a Recirculating Raft Aquaponic System

Abstract: Aquaponics is an integrated fish and plant recirculating production system. Solid fish waste must be removed from the production system to maintain optimal water quality parameters for fish and plant health. The University of the Virgin Islands (UVI) raft aquaponic system's primary treatment device for solids removal is a cylindro-conical clarifier; however, alternative mechanical filtration devices such as a parabolic screen filter (PSF) may offer advantages. The objectives of the elevenweek experiment were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 19 publications
2
19
1
Order By: Relevance
“…There were no significant differences ( P ≥ 0.05) between treatments for temperature, oxygen, pH, alkalinity, EC, TAN, NO 2 ‐N, and NO 3 ‐N (Table ). All aforementioned parameters were within optimal ranges for a raft aquaponic system producing tilapia (Rakocy ; Al‐Hafedh et al ; Danaher et al ). There was no significant difference ( P ≥ 0.05) between treatments for TSS concentration entering or exiting either primary filtration device (Table ).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…There were no significant differences ( P ≥ 0.05) between treatments for temperature, oxygen, pH, alkalinity, EC, TAN, NO 2 ‐N, and NO 3 ‐N (Table ). All aforementioned parameters were within optimal ranges for a raft aquaponic system producing tilapia (Rakocy ; Al‐Hafedh et al ; Danaher et al ). There was no significant difference ( P ≥ 0.05) between treatments for TSS concentration entering or exiting either primary filtration device (Table ).…”
Section: Resultsmentioning
confidence: 93%
“…Aquaponics is the combined culture of fish and plants in a recirculating aquaculture system and has received considerable attention as a result of the system's capability to raise fish at high density, sustain water quality, minimize water exchange, and produce a marketable vegetable crop (Rakocy ; Adler et al ; Al‐Hafedh et al ; Graber and Junge ; Danaher et al ). The vegetable crop is responsible for the direct assimilation of dissolved fish wastes and products of microbial breakdown in the recirculating aquaponic system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Danaher et al . () compared a PSF with a cylindro‐conical clarifier used in a UV aquaponic system and found that the PSF was able to remove 5.8% of the solids entering it when compared with a 30.8% removal efficiency for clarifier. Through PSF filtration, removing residual feed, excrement and other large solid particles at the beginning of system operation can greatly reduce the load of the entire water treatment system and, in particular, could greatly improve the foam separation and biological filtration processes treatment effect.…”
Section: Physical Filtration Equipments Of Rassmentioning
confidence: 99%
“…In these integrated systems, nutrients that are excreted by the fish or generated by microbial activity (Munguia-Fragozo et al, 2015;Zou et al, 2016a) are absorbed by hydroponically cultured plants, thus treating the water before it is recycled to the fish tank (Endut et al, 2009;Tyson et al, 2011;Nichols and Savidov, 2012;Medina et al, 2016;Nuwansi et al, 2016). AP has received considerable attention due to its capability to sustain water quality, minimise fresh water consumption, and provide a marketable vegetable crop (McMurtry et al, 1997a(McMurtry et al, , 1997bAdler et al, 2000a;Lennard and Leonard, 2005;Graber and Junge, 2009;Danaher et al, 2011Danaher et al, , 2013Pantanella et al, 2011Pantanella et al, , 2015Espinosa Moya et al, 2016;Shete et al, 2016). Nevertheless few microbial studies have been conducted to determine food safety status (Elumalai et al, 2017) suggesting that further research is needed to evaluate this aspect.…”
Section: Introductionmentioning
confidence: 99%